2020
DOI: 10.1242/dev.194274
|View full text |Cite
|
Sign up to set email alerts
|

The RNA dependent DNA methylation pathway is required to restrict SPOROCYTELESS/NOZZLE expression to specify a single female germ cell precursor in Arabidopsis

Abstract: In higher plants the female germline is formed from the megaspore mother cell (MMC), a single cell in the pre-meiotic ovule. Previously, it was reported that mutants in RNA dependent DNA methylation - RdDM - pathway might be involved in restricting female germline to a single nucellus cell. We show that the DRM methyltransferase double mutant drm1drm2 also presents also presents ectopic enlarged cells, consistent with supernumerary MMC-like cells. In wild-type ovules MMC differentiation required SPOROCYTELESS/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 47 publications
4
52
1
Order By: Relevance
“…Moreover, our BLAST searches revealed that factors influencing chromatin state as transposon-related sequences, histone methyl-and acetyltransferases, histone 3.3 and ATP dependent DNA helicases (SUVH1 and HAC) [83,84], were related to DMCs preferentially hypermethylated at CHH context at this stage of development. Genetic evidence indicates that RNA-dependent DNA methylation (RdDM), which produces de novo CHH methylation at transposon edges, euchromatin, or at heterochromatin/euchromatin boundaries, might also influence megasporogenesis [85,86] as it was found to be involved in MMC specification and differentiation [43,87]. Moreover, recent comparative transcriptome analysis of P. notatum and Hypericum perforatum L. aposporic model systems found several genes involved in RdDM as differentially expressed between apomictic and sexual genotypes [49,88].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our BLAST searches revealed that factors influencing chromatin state as transposon-related sequences, histone methyl-and acetyltransferases, histone 3.3 and ATP dependent DNA helicases (SUVH1 and HAC) [83,84], were related to DMCs preferentially hypermethylated at CHH context at this stage of development. Genetic evidence indicates that RNA-dependent DNA methylation (RdDM), which produces de novo CHH methylation at transposon edges, euchromatin, or at heterochromatin/euchromatin boundaries, might also influence megasporogenesis [85,86] as it was found to be involved in MMC specification and differentiation [43,87]. Moreover, recent comparative transcriptome analysis of P. notatum and Hypericum perforatum L. aposporic model systems found several genes involved in RdDM as differentially expressed between apomictic and sexual genotypes [49,88].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in line with a formerly proposed canalization process operating during SMC establishment ( Grossniklaus and Schneitz, 1998 ; RodrĂ­guez-Leal et al, 2015 ). Despite the fact that several mutations (reviewed in Pinto et al, 2019 ; Mendes et al, 2020 ), including kat (this study), alter SMC singleness in Arabidopsis, canalization remains a robust process securing the formation of a single embryo sac despite such genetic perturbations. How this developmental mechanism buffers phenotypic inter-individual variations and whether it is evolutionary constrained remains to be determined.…”
Section: Discussionmentioning
confidence: 95%
“…Although SMC singleness may appear to be robust, more than one SMC candidate per primordium is occasionally seen, yet at different frequencies depending on the specific Arabidopsis accession (~5% in Landsberg erecta [L er ], 10% in Columbia [Col-0], 27% in Monterrosso [Mr-0]), ( Grossniklaus and Schneitz, 1998 ; RodrĂ­guez-Leal et al, 2015 ). Arabidopsis , maize, and rice mutants in which SMC singleness is compromised have unveiled the role of regulatory pathways involving intercellular signaling, small RNAs, as well as DNA and histone methylation ( Garcia-Aguilar et al, 2010 ; Mendes et al, 2020 ; Nonomura et al, 2003 ; Olmedo-Monfil et al, 2010 ; Schmidt et al, 2011 ; Sheridan et al, 1996 ; Sheridan et al, 1999 ; Su et al, 2020 ; Su et al, 2017 ; Zhao et al, 2008 ). As the SMC forms, cell-cycle regulation contributes to the stabilization of its fate in a cell-autonomous manner through cyclin-dependent kinase (CDK) inhibitors and RETINOBLASTOMA-RELATED1 (RBR1) ( Cao et al, 2018 ; Zhao et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In wild type Arabidopsis, one cell of the hypodermal ovule layer is specified as the MMC. In the double drm1 drm2 mutant, multiple cells become specified as the MMC, resulting in multiple precursors of the female gametophyte (Mendes et al, 2020; Figure 2). Here, loss of DRM function causes upregulation of the SPOROCYTELESS/NOZZLE (SPL/NZZ) transcript encoding a protein involved in balancing the reproductive cell fate establishment in the premeiotic ovule (Mendes et al, 2020).…”
Section: Defects In Reproductive Development Of Dna Methylation Mutantsmentioning
confidence: 99%
“…In the double drm1 drm2 mutant, multiple cells become specified as the MMC, resulting in multiple precursors of the female gametophyte (Mendes et al, 2020; Figure 2). Here, loss of DRM function causes upregulation of the SPOROCYTELESS/NOZZLE (SPL/NZZ) transcript encoding a protein involved in balancing the reproductive cell fate establishment in the premeiotic ovule (Mendes et al, 2020). A similar phenotype develops in mutants of the AGO4, AGO6, AGO8 and AGO9 genes (shown for AGO4 in Figure 2), and depending on the mutated gene, the number of MMCs varies, from two to four (HernĂĄndez-Lagana et al, 2016).…”
Section: Defects In Reproductive Development Of Dna Methylation Mutantsmentioning
confidence: 99%